Peopling Europe through Data Practices: Introduction to the Special Issue. (March 2020) - Cakici, Baki; Ruppert, Evelyn; Scheel, Stephan
Politically, Europe has been unable to address itself to a constituted polity and people as more than an agglomeration of nation-states. From the resurgence of nationalisms to the crisis of the single currency and the unprecedented decision of a member state to leave the European Union (EU), core questions about the future of Europe have been rearticulated: Who are the people of Europe? Is there a European identity? What does it mean to say, "I am European?" Where does Europe begin and end? and Who can legitimately claim to be a part of a "European" people? The special issue (SI) seeks to contest dominant framings of the question "Who are the people of Europe?" as only a matter of government policies, electoral campaigns, or parliamentary debates. Instead, the contributions start from the assumption that answers to this question exist in data practices where people are addressed, framed, known, and governed as European. The central argument of this SI is that it is through data practices that the EU seeks to simultaneously constitute its population as a knowable, governable entity, and as a distinct form of peoplehood where common personhood is more important than differences.